2017
DOI: 10.1002/jms.4032
|View full text |Cite
|
Sign up to set email alerts
|

Screening of exon methylation biomarkers for colorectal cancer via LC‐MS/MS strategy

Abstract: The identification of biomarkers would be of benefit for the diagnosis and treatment of colorectal cancer. DNA methylation in specific genomic regions, which had shown strongly association with disease genotypes, was an effective indicator to reveal the occurrence and development of cancers. To screen out methylation biomarkers for colorectal cancer (CRC), genomic DNA was isolated from colorectal cancerous and corresponding cancer-adjacent tissues collected from 30 CRC patients and then bisulfite-converted. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
6
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 25 publications
2
6
0
2
Order By: Relevance
“…RUNX associates with the Wnt oncogenic and TGF- β tumour suppressive pathways to promote CRC development [31]. The role of RUNX3 methylation has also been examined for diagnostic value in CRC in multiple studies [19–22, 32]. Huang et al determined RUNX3 methylation levels in 30 colorectal cancer tissues and their paired adjacent normal tissues, showing that the RUNX3 methylation levels were significantly higher in tumour than in adjacent tissues (28% vs. 15%, P < 0.01) [19].…”
Section: Dna Methylation Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…RUNX associates with the Wnt oncogenic and TGF- β tumour suppressive pathways to promote CRC development [31]. The role of RUNX3 methylation has also been examined for diagnostic value in CRC in multiple studies [19–22, 32]. Huang et al determined RUNX3 methylation levels in 30 colorectal cancer tissues and their paired adjacent normal tissues, showing that the RUNX3 methylation levels were significantly higher in tumour than in adjacent tissues (28% vs. 15%, P < 0.01) [19].…”
Section: Dna Methylation Markersmentioning
confidence: 99%
“…The role of RUNX3 methylation has also been examined for diagnostic value in CRC in multiple studies [19–22, 32]. Huang et al determined RUNX3 methylation levels in 30 colorectal cancer tissues and their paired adjacent normal tissues, showing that the RUNX3 methylation levels were significantly higher in tumour than in adjacent tissues (28% vs. 15%, P < 0.01) [19]. Shin et al also observed that tissue RUNX3 hypermethylation had a sensitivity of 32.3% (20/62) and a specificity of 100.0% (0/10) for CRC detection.…”
Section: Dna Methylation Markersmentioning
confidence: 99%
“…It has been described that CRIP1a may act as a presynaptic modulator of neurotransmitter release and also in mediation of long-term depression of synaptic responses(54)(55)(56)(57); It regulates CB1 activity upon agonist or antagonist binding as well as CB1 internalization(58,59, 32); suppresses CB1-mediated tonic inhibition of voltage-gated Ca 2+ channels (32); enhances CB1R signaling and diminishes the severity of chemically induced acute epileptiform seizure upon induced overexpression in vivo in the mouse hippocampus(54); reduces the proliferative and migration abilities of colon cancer cells upon induced overexpression in vitro(60). CNRIP1 downregulation (due to hyper-methylation of its promoter) is a biomarker in some cancers, such as adenomas, gastric cancer, non-Hodgkin lymphoma and cholangiocarcinoma(61)(62)(63)(64)(65)(66). Functional data from the literature above described, besides the expression data herein presented, indicate CNRIP1 as a putative deafness gene.…”
mentioning
confidence: 99%
“…To address this issue, we adopted a LC-MS/MS approach in present study, which was recently reported [ 30 , 32 ]. Although the LC-MS/MS method can’t distinguish the methylation status of single CpG, it can provide an average methylation level across all CpG sites of a target region and make it easy to compare the methylation alteration between different samples.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, methylation alteration of exon-based gene body has attracted more attention since GbM was found that frequently occurred in some oncogenic genes and DNA methylation in transcribed regions were also correlated with gene expression [ 25 , 26 ]. It would provide more detectable loci and may be novel biomarkers or therapeutic targets in cancer [ 26 , 32 ]. Here, our study observed that the methylation level of p16 gene body had high sensitivity and specificity as potential CRC biomarker, and the hypermethylation of p16 exon 1 or exon 2 was associated with N/Dukes or T staging.…”
Section: Discussionmentioning
confidence: 99%